Improving The Quality of Life of Patients with Diabetes Mellitus Type 2 with Treatment Adherence - Yuli Wahyuni (Universitas Muhammadiyah Semarang, 2021)
Diabetes is a complex, chronic illness requiring continuous medical care with a multifactorial risk reduction strategy beyond glycemic control. Quality of life in type 2 diabetes mellitus(DM) is one indicator of successful disease management. This study aimed to determine the extent to which medication adherence affects the quality of life. The method used by searching the literature of scientific publications in the time of years between 2016-2021 using the Pubmed database, Science Direct, Cinahl, Willey Online Library and google scholar, there were 2.281articles. The result of the literature review found nine articles that fit inclusion and exclusion criteria, it was found that several variables can improve the quality of life in type 2 DM, one of which is treatment adherence. Treatment adherence is a major predictor in improving the quality of life in type 2 DM when compared with other variables. It is important to develop DM management interventions that focus on improving treatment adherence.